A Novel Design of Temporomandibular Joint Prosthesis for Lateral Pterygoid Muscle Attachment: A Preliminary Study - Zou, Luxiang; Zhong, Yingqian; Xiong, Yinze; He, Dongmei; Li, Xiang; Lu, Chuan; Zhu, Huimin (Frontiers in Bioengineering and Biotechnology, 2021)
Introduction: In temporomandibular joint (TMJ) replacement operation, due to the condylectomy, the lateral pterygoid muscle (LPM) lost attachment and had impact on the mandible kinematic function. This study aimed to design a novel TMJ replacement prosthesis for LPM attachment and to verify its feasibility by preliminary in vitro and in vivo experiments. Materials and methods: An artificial TMJ prosthesis designed with a porous structure on the condylar neck region for LPM attachment was fabricated by a 3D printed titanium (Ti) alloy. A rat myoblast cell line (L6) was tested for adhesion and biocompatibility with porous titanium scaffolds in vitro by cell counting Kit-8 (CCK-8), scanning electron microscope (SEM), flow cytometry (FCM), real-time polymerase chain reaction (RT-PCR), immunocytofluorescense, western blotting, etc. The porous titanium scaffolds were further embedded in the rat intervertebral muscle to analyze muscle growth and biomechanical strength in vivo. The novel artificial TMJ prosthesis was implanted to reconstruct the goat’s condyle and LPM reattachment was analyzed by hard tissue section and avulsion force test. Results: L6 muscle cells showed good proliferation potential on the porous Ti scaffold under SEM scanning and FCM test. In Rt-PCR, immunocytofluorescense and western blotting tests, the L6 cell lines had good myogenic capacity when cultured on the scaffold with high expression of factors such as Myod1 and myoglobin, etc. In the in vivo experiment, muscles penetrated into the porous scaffold in both rats and goats. In rat’s intervertebral muscle implantation, the avulsion force was 0.716N/mm2 in 4 weeks after operation and was significantly increased to 0.801N/mm2 at 8 weeks (p <0.05). In goat condylar reconstruction with the porous scaffold prosthesis, muscles attached to the prosthesis with the avulsion force of 0.436N/mm2 at 8 weeks, but was smaller than the biological muscle-bone attachment force. Conclusion: The novel designed TMJ prosthesis can help LPM attach to its porous titanium scaffold structure area for future function.